1995
DOI: 10.1002/glia.440140408
|View full text |Cite
|
Sign up to set email alerts
|

Three different thyroid hormone receptor isoforms are detected in a pure culture of ovine oligodendrocytes

Abstract: Thyroid hormones are important for the normal development of the central nervous system. In humans, the period around the end of the intrauterine life and the first few months of neonatal life is critically dependent on the presence of normal amounts of thyroid hormone. There are significant events occurring during this time; myelination is one. Myelin is synthesized by oligodendrocytes. A panel of site-specific polyclonal antibodies against alpha-1 thyroid hormone receptor (TR), alpha-2 variant TR, and beta-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 42 publications
3
17
1
Order By: Relevance
“…Most of the literature on nuclear receptors in glia has so far been concerned with cataloguing. As evident from (Barres et al, 1994;Fierro-Renoy et al, 1995) Constitutive in culture, downregulated in mature cells (Barakat-Walter et al, 1993) RAR RAR␣ constitutive, RAR␤ inducible, RAR␥ - (Laeng et al, 1994) Not analyzed PPAR PPAR␦ϩ, PPAR␥Ϫ (Granneman et al, 1998) PPAR␦ high levels, PPAR␥ low levels (Granneman et al, 1998) GR, glucocorticoid receptor, MR, mineralocorticoid receptor; AR, androgen receptor; PR, progesterone receptor; ER, estrogen receptor; TR, thyroid hormone receptor; RAR, retinoic acid receptor; PPAR, peroxisome proliferator-activated receptor.…”
Section: Nuclear Receptorsmentioning
confidence: 61%
“…Most of the literature on nuclear receptors in glia has so far been concerned with cataloguing. As evident from (Barres et al, 1994;Fierro-Renoy et al, 1995) Constitutive in culture, downregulated in mature cells (Barakat-Walter et al, 1993) RAR RAR␣ constitutive, RAR␤ inducible, RAR␥ - (Laeng et al, 1994) Not analyzed PPAR PPAR␦ϩ, PPAR␥Ϫ (Granneman et al, 1998) PPAR␦ high levels, PPAR␥ low levels (Granneman et al, 1998) GR, glucocorticoid receptor, MR, mineralocorticoid receptor; AR, androgen receptor; PR, progesterone receptor; ER, estrogen receptor; TR, thyroid hormone receptor; RAR, retinoic acid receptor; PPAR, peroxisome proliferator-activated receptor.…”
Section: Nuclear Receptorsmentioning
confidence: 61%
“…Recent work has shown that T 3 blocks proliferation of OPCs and induces their differentiation [Baas et al, 1997]. Studies have determined that three T 3 receptor isoforms are expressed in the oligodendrocyte lineage: · 1 , · 2 , and ß 1 [Fiero-Renoy et al, 1995]. Interestingly, T 3 receptors · 1 and · 2 are expressed in both OPCs and differentiated oligodendrocytes, but the T 3 receptor ß 1 is only expressed in differentiated oligodendrocytes [Baas et al, 1998;Carre et al, 1998].…”
Section: Discussionmentioning
confidence: 99%
“…Both developing and mature oligodendrocytes express thyroid hormone receptors (Yusta et al, 1988, Fierro-Renoy et al, 1995, Baas et al, 2002). There appears to be sequential expression of the TRα and TRβ gene products such that all oligodendrocytes express the alpha receptors but only mature oligodendrocytes express the beta receptors (Baas et al, 1994, Carre et al, 1998).…”
Section: Hormonal Factorsmentioning
confidence: 99%